Modelling,Characterisation And Force Tracking Control Of A Magnetorheological Damper Under Harmonic Excitation - Abdul Kadir, Faizul Akmar; Hudha, Khisbullah; Sabino, Ubaidillah (Inderscience, 2011)

(untitled)
The objective of this paper is to study the performance of a sixth order polynomial approach to model hysteresis behaviour of a magnetorheological (MR) damper under harmonic excitations.The polynomial model is developed based on curve fitting from the experimental results and consists of a pair subsystem namely positive and negative acceleration which correspond to the upper and lower curves.The performance of the proposed polynomial model is compared with a well known non-parametric technique namely inverse model.The energy dissipated and equivalent damping coefficient of the MR damper in terms of input current and displacement amplitude are investigated.From the simulation results,the sixth order polynomial model shows better performance in describing non-linear hysteresis behaviour of the MR damper compared with inverse model.The force tracking control in both simulation and experimental studies demonstrate that a close-loop PI control has the ability to track the desired damping force well.